2016
DOI: 10.33585/cmy.68206
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of filamentous and yeast fungi in soil of citrus and grapevine plantations in the Assiut region, Egypt.

Abstract: An extensive survey of soil mycobiota on citrus and grapevine plantations in Sahel-Saleem City, Assiut Governorate, Egypt was carried out using the dilution-plate method and 2 isolation media at 25°C. Sixty-four genera and 195 species of filamentous fungi and 10 genera and 13 species of yeasts were recovered. A higher diversity (number of genera and species) and gross total counts were recovered from citrus than from grapevine soil. The peak of filamentous fungi recovered from both soils was found to be in Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Our previous experience (Abdel-Sater et al 2016, Moubasher et al 2017 revealed that zygomycetes prevailed on most of the isolation media used, therefore the first two media were finally chosen since both contained dichloran, which restricts mucoraceous growth without affecting other species (King et al 1979, Hocking & Pitt 1980. The first medium (a w = 1.0) was used as a general isolation medium (King et al 1979), the second (a w = 0.95) for xerotolerant fungi and the third (a w = 0.89) for xerophilic ones (Gunde-Cimerman et al 2000, Butinar et al 2005.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous experience (Abdel-Sater et al 2016, Moubasher et al 2017 revealed that zygomycetes prevailed on most of the isolation media used, therefore the first two media were finally chosen since both contained dichloran, which restricts mucoraceous growth without affecting other species (King et al 1979, Hocking & Pitt 1980. The first medium (a w = 1.0) was used as a general isolation medium (King et al 1979), the second (a w = 0.95) for xerotolerant fungi and the third (a w = 0.89) for xerophilic ones (Gunde-Cimerman et al 2000, Butinar et al 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Then these bands were eluted and sequenced. Each sample was sequenced in both directions (Abdel-Sater et al 2016). Raw sequences were assembled in contigs with the CLCBio Main Workbench program.…”
Section: Methodsmentioning
confidence: 99%
“…The genomic DNA of Fusarium isolate was extracted using the cetyltrimethyl ammonium bromide method. Universal internal transcribed spacer (ITS) primers ITS1 and ITS4 were used for the amplification of ~520 bp rDNA fragments using a polymerase chain reaction (PCR) as described by Abdel-Sater et al (2016). The Basic Local Alignment Search Tool of Nucleotides program was used to compare the sequences and to retrieve the homologous nucleotide sequences from the National Center for Biotechnology Information (NCBI) database (www.ncbi.nlm.nih.gov/BLAST/).…”
Section: Fungal Strain Isolation and Identificationmentioning
confidence: 99%
“…Quambalaria cyanescens has been isolated from a broad range of ecological niches, including air, plant materials, soil and insects from several countries in North Africa, North America, South Asia, Australia, Europe and the Middle East (de Hoog & de Vries 1973, Kolařík et al 2006, Abdel-Sater et al 2016 pova et al 2014). This fungal species, as a potential opportunistic pathogen in immunocompromised or debilitated patients, has also been isolated from blood, human skin and hospital-acquired infections in individuals with pneumonia, peritoneal inflammation and invasive pulmonary infection (Jackson et al 1990, Tambini et al 1996, Fan et al 2014, Kuan et al 2015.…”
Section: Ecology and Future Prospectsmentioning
confidence: 99%